Development of an Integrated Service Unit Management Model to Optimize Public Services at Universitas Negeri Manado - Watulingas, Marcia Imelda; Katuuk, Deitje Adolfien; Lumapouw, Harold Refly; Lengkong, Jeffry (JR Education, 2024)
This research aims to describe ULT Unima from the planning, implementation, monitoring, and evaluation to its management development. This type of research is a case study to examine contemporary phenomena entirely and comprehensively in actual conditions, using a descriptive approach. This research was carried out at the Unima Integrated Services Unit in March 2023. Research data was collected using observation, interviews, and documentation methods. Data analysis in this research uses data reduction techniques, data presentation, and conclusion presentation. The results can create quality, efficiency, and responsiveness of the services provided. The research results obtained, (1) ULT planning, most of the planning stages have been implemented, but stages such as revising technical guidelines/service procedures, employee training, monitoring, and evaluation have not been implemented, (2) ULT implementation, has not fully referred to implementation theory or has not yet been fully implemented. optimally carried out, such as services carried out by ULT Officers not referring to guidelines because there were no ULT SOPs and other service SOPs at the start, (3) ULT supervision, not carried out because there was no request from superiors as accountability, (4) ULT evaluation, not yet carried out evaluation that refers to these theories, where evaluation activities are carried out systematically, gradually and measurably. A manifestation of the implementation of service management at ULT Unima is the development of Public Service Standards, and several standard operating procedures (SOPs) such as Data Request SOPs, Cooperation SOPs, and General SOPs. Apart from that, a service tutorial was also created on ULT Unima as guidance and information on existing services.